The Influence of Consumer Impulse Buying and Electronic Word of Mouth on Purchasing Decisions - Tasya Gita, Meisa; Satriawan, Budhi; Satyawisudarini, Inne (International Journal of Advanced Multidisciplinary, 2023)
This study aims to analyze or find out about conditions and how much influence Consumer Impulse Buying and Electronic Word Of Mouth have on purchasing decisions through surveys of consumers of Skincare Avoskin Yourbae Serum products on TikTok. Impulse buying is the tendency of consumers to make purchases spontaneously, unreflected, in a hurry driven by the psychological emotional aspects of a product and tempted by persuasion from marketers. Electronic Word Of Mouth is an informal, non- commercial online communication about opinions on a service or product, which occurs in person, by telephone, e-mail, or other communication method. Purchasing decisions are decisions where consumers actually decide to buy and enjoy goods or services among various alternative choices. Based on the results of this study, it shows that Consumer Impulse Buying is considered quite good by consumers and has a positive and significant effect on Purchase Decisions. Electronic Word of Mouth is considered good by consumers and has a positive and significant effect on Purchasing Decisions. Consumer Impulse Buying and Electronic Word of Mouth have a positive and significant effect on Consumer Purchase Decisions on Avoskin Yourbae Serum Skincare Products on TikTok and are considered to have a partial and simultaneous effect, because with the ability of companies to utilize and create Consumer Impulse Buying and Electronic Word of Mouth, it will have an impact consumer purchasing decisions for Avoskin products, especially Skincare Avoskin Yourbae Serum.